Analisis kesiapan guru dalam mengimplementasikan kurikulum merdeka tahap mandiri berubah di sekolah dasar - Ama Tullah Lina Mufida; Rukayah rukayah; Sandra Bayu Kurniawan (Didaktika Dwija Indria, 2023)
Changing the curriculum to become an independent curriculum is based on a condition called learning loss which is caused by the loss of emotional bonds between teachers and students due to distance learning. Implementation of the Independent Curriculum certainly cannot be separated from various problems and challenges. One of them is the readiness of the teacher. This research is included in the descriptive study which aims to describe the readiness of teachers to implement the independent phase of the changing independent curriculum. The subjects in this study were class I teachers and class IV teachers. Data collection was carried out by observation, interview and documentation techniques. The triangulation technique is used as a validity test with the data analysis used, namely the Interactive Technique, the Miles and Huberman analysis model. The results of the study show that, First, in learning planning, of course, there is still confusion because the Independent Curriculum is relatively new, so teachers still need to learn and adapt. Second, judging from the ability of teachers who have not been optimal in implementing independent curriculum learning. in using the learning model the teacher has not fully implemented creative, innovative and enjoyable learning in accordance with the meaning of the independent curriculum. third, in the Free Learning Curriculum, assessment is not so difficult to apply. The implication that arises from this research is that teacher readiness plays an important role in the successful implementation of the curriculum.